the Comparison of Anxiety Levels of Male Volleyball Athletes Before and After Competing in the 2025 Unhasa Cup Volleyball Championship - Rosalina, Rosi; Zulfata, Rachma (Universitas Hamzanwadi, 2025)
This research method uses a quantitative descriptive research design. The population in this study consists of 32 teams comprising 384 male volleyball players. The sample for this study consists of male volleyball athletes who participated in and advanced to the semifinals of the Unhasa Cup 2025 championship, totaling 4 teams, with each team comprising 12 players, resulting in a total of 48 athletes in this study. The instruments used were the Sport Competition Anxiety Test (SCAT), and data analysis was conducted using the SPSS application. The research results showed an average pretest score of 21.98 and a posttest score of 17.42. The number of respondents was 48 students. Since the average pretest score of 21.98 is greater than the posttest score of 17.42, this indicates a significant difference in the average anxiety levels before and after the intervention. From the paired samples test above, the significance (two-tailed) is < 0.000 < 0.05, so H0 is rejected and Ha is accepted. The calculated t-value is 8.239 with a degree of freedom (df) of 47. From the comparison between the calculated t-value and the table t-value, it is evident that the calculated t-value of 8.239 is greater than the table t-value of 2.011. Therefore, based on the decision-making criteria above, it can be concluded that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a difference in the average scores between the pretest and posttest results, indicating an effect on the reduction in anxiety levels before and after the match.